2020
DOI: 10.7554/elife.55474
|View full text |Cite
|
Sign up to set email alerts
|

An atlas of cell types in the mouse epididymis and vas deferens

Abstract: Following testicular spermatogenesis, mammalian sperm continue to mature in a long epithelial tube known as the epididymis, which plays key roles in remodeling sperm protein, lipid, and RNA composition. To understand the roles for the epididymis in reproductive biology, we generated a single-cell atlas of the murine epididymis and vas deferens. We recovered key epithelial cell types including principal cells, clear cells, and basal cells, along with associated support cells that include fibroblasts, smooth mus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 110 publications
(142 reference statements)
8
74
0
Order By: Relevance
“…Consistent with a recent study 37 , epididymal supporting cells were also identified. These include myoid cells/fibroblasts (C1) for contraction of the myoid to promote sperm movement and form an extracellular environment 2 , 37 , 51 , macrophages/monocytes (C3) for immune equilibrium 52 , and endothelial cells (C6) for composing blood and lymph vessels 37 . In addition to epididymal cells, sperm (C7) were also identified because of the whole epididymis dissociation applied in our study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with a recent study 37 , epididymal supporting cells were also identified. These include myoid cells/fibroblasts (C1) for contraction of the myoid to promote sperm movement and form an extracellular environment 2 , 37 , 51 , macrophages/monocytes (C3) for immune equilibrium 52 , and endothelial cells (C6) for composing blood and lymph vessels 37 . In addition to epididymal cells, sperm (C7) were also identified because of the whole epididymis dissociation applied in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Accumulating studies have attempted to characterize the cell types in the epididymis based on cell location, morphology, connection, function, and marker gene expression 34 36 . A scRNA-seq dataset from the mouse genital duct was recently reported 37 . While our results are consistent with a previous report on the clustering of general cell types, our study provided an in-depth analysis of biological replicates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was excluded from further analysis. Finally, we identified two clusters (P.Epi and B.Epi) as basal epididymal cells and principal epididymal cells based on marker genes (fig S2b) (Rinaldi et al, 2020). Because the epididymis is located close to the EPI depot, epididymal cells included in the EPI adipose are likely a dissection artifact, and they were not included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The epididymis plays critical roles in sperm maturation, transport, storage, and protection by providing a suitable microenvironment [24][25][26]. The distinct segments are closely associated with the epididymal functions [27]. Male gametes leave the testis in a functionally immature status.…”
Section: Introductionmentioning
confidence: 99%